Fabrication of graphene-encapsulated Na3V2(PO4)3 as high-performance cathode materials for sodium-ion batteries. Issue 49 (3rd May 2016) - Tao, Shi; Wang, Xingbo; Cui, Peixin; Wang, Yu; Haleem, Yasir A.; Wei, Shenghui; Huang, Weifeng; Song, Li; Chu, Wangsheng
Abstract : A thin layers graphene-encapsulated Na3 V2 (PO4 )3 (NVP/G) has been in the spotlight as a potential candidate of next generation batteries to compensate the intrinsic low electronic conductivity of NVP and strengthen its structure stable. Abstract : Na3 V2 (PO4 )3 (NVP) has been in the spotlight as a potential candidate of next generation batteries to overcome the limitation of lithium resources on Earth. Here a thin-layer graphene-encapsulated NVP composite (NVP/G) was synthesized by self-assembly of surface modified NVP and graphene oxide and then followed by reduction to compensate for the intrinsic low electronic conductivity of NVP and strengthen its structure stability. The as-synthesized hybrid composite as a cathode for sodium-ion batteries (SIBs) exhibits excellent high specific capacity and superior rate performance with discharge capacities of 115.2 mA h g −1 at 0.2 C and 70.1 mA h g −1 at 30 C, It also shows an excellent cycling stability with about 86.0% capacity retention at 5 C after 300 cycles. Ex situ X-ray absorption spectroscopy (XAS) characterization confirmes the local geometrical environment around vanadium is highly conserved during the sodiation/desodiation process, associated with an electrochemically active V 3+ /V 4+ redox couple. Hence the as-prepared hybrid composite can be considered as a promising cathode material for high-rate SIBs, thanks to the effect interface interaction between NVP nanoparticle sand graphene films.